Uji Efektivitas Ekstrak Jahe Merah (Zingiber Officinale Var Rubrum) pada Meencit terhadap Penurunan Kadar Gula Darah - Meri Listina; Rosalia Putri; Mansura Feby Amanda (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Persistent elevation of blood glucose levels defines diabetes mellitus, a chronic metabolic disorder that occurs when insulin production is insufficient, diminished sensitivity of insulin receptors, or a combination of both factors. The medicinal properties of red ginger (Zingiber officinale var. rubrum) are attributed to its rich content of bioactive compounds, including gingerol and shogaol, which are considered key contributors to its various therapeutic effects. The effectiveness of red ginger extract in lowering blood glucose levels in experimental mice was evaluated in this study. A true experimental design with a quantitative approach was applied, employing a pretest–posttest control group format. The study involved twelve samples, which were randomly allocated into four separate groups. The treatment phase was conducted over a period of seven days. Findings revealed mean values of 10.4 prior to the intervention and 15.2 afterward, indicating a notable increase. A significant difference between pre-treatment and post-treatment measurements in group K1 was revealed by the statistical analysis, which yielded a P-value of 0.001 (P < 0.05). It was observed that red ginger extract, given at 100 mg per kilogram of body weight, effectively reduced blood glucose levels in the mice studied..